TRANSFORMATIONAL LEADERSHIP IN IMPROVING THE QUALITY OF EDUCATION IN ISLAMIC BOARDING SCHOOL - Siti Nur Aviatun Hasanah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to analyze the role of transformational leadership in improving the quality of education in Islamic boarding schools. Transformational leadership emphasizes the leader's ability to inspire, motivate, and guide his followers to achieve their best potential. This study uses a descriptive qualitative approach with informants consisting of kiai, teachers, and students, and data collection techniques through in-depth interviews, participant observation, and documentation. The results show that the application of the four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individual consideration can improve students' learning motivation, discipline, creativity, critical thinking skills, and teacher professionalism. Additional strategies such as a collaborative learning culture and strengthening Islamic boarding school values also support the creation of holistic education. Despite challenges such as differences in student character and limited resources, transformational leadership has proven effective in improving the quality of education in Islamic boarding schools and can serve as a model for other Islamic boarding school managers.